Study of Memory Cell Architectures in QCA Technology (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
CMOS technology is experiencing power dissipation, short channel effects and quantum effects problems with its relation to chip size, which makes it too hard for integrating more transistors, reaching its scaling limits. Quantum Dot Cellular Automata (QCA) is one of emerging nanotechnologies in recent times to overcome this flaw. The QCA technology is used for designing and implementation of digital circuits efficiently due to its features like smaller feature size, high speed, low power dissipation and high switching frequency. These characteristics prompt memory cell architecture and implementation in QCA as an appealing choice for manufacturing storage devices. This paper discusses architectures of several line and loop based memory cells to compare in terms of density, low power, complexity and switching frequency and to deduce an architecture method which is significant for designing memory cells